(untitled) (Journal of Geography and Environmental Management, 2016)
The scientific article reviews the methods for determining environmental flows in the lower reaches of large rivers, include transboundary rivers. The paper presents a critical analysis of methodologies for calculating environmental flows based near and far abroad on publications, as well as publications in the Republic of Kazakhstan.